2016
DOI: 10.17487/rfc7964
|View full text |Cite
|
Sign up to set email alerts
|

Solutions for BGP Persistent Route Oscillation

Abstract: Routing information reduction by BGP Route Reflection or Confederation can result in persistent internal BGP route oscillations with certain routing setups and network topologies. This document specifies two sets of additional paths that can be used to eliminate these route oscillations in a network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Methods of detection of BGP AS path loops have been studied by Refs. [18,19]. Moreover, the private AS number leaking in BGP AS path information has also been mentioned by Refs.…”
Section: Related Workmentioning
confidence: 91%
“…Methods of detection of BGP AS path loops have been studied by Refs. [18,19]. Moreover, the private AS number leaking in BGP AS path information has also been mentioned by Refs.…”
Section: Related Workmentioning
confidence: 91%
“…Many studies have addressed the oscillations and looping problems of IBGP (e.g., [3], [16], [17], [31], [34], [44]). Over the years, the BGP specification has been augmented to account for the use of route reflectors and has added more path attributes in an attempt to avoid routing loops due to route reflectors [4].…”
Section: B Bgp Analysis and Extensionsmentioning
confidence: 99%
“…In Walton et al [13] solution, a reflector finds one best path through each of the neighboring AS and advertises this per AS best path if this path's local preference and AS sequence length values are equal to the reflector's overall best path's corresponding attributes. Basu et al [12] have showed a counter-example to Walton's solution.…”
Section: Med-induced Divergencementioning
confidence: 99%
“…That is, the system progresses normally according to its routing policies, unless divergence occurs. Furthermore, contrary to other proposed solutions [9], [12], [13], our approach preserves the efficiency of iBGP by having each reflector disseminate only a single path to each of its peers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation